The Efficacy And Safety Of Aspirin As The Primary Prevention Of Cardiovascular Disease: An Updated Meta-Analysis - Xie W; Luo Y; Liang X; Lin Z; Wang Z; Liu M (Dove Medical Press, 2019)
Wenchao Xie,1 Ying Luo,2 Xiangwen Liang,1 Zhihai Lin,1 Zhengdong Wang,1 Ming Liu1 1Department of Cardiology, Sixth Affiliated Hospital of Guangxi Medical University, Yulin, Guangxi 537000, People’s Republic of China; 2Graduate School, Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of ChinaCorrespondence: Ming LiuDepartment of Cardiology, Sixth Affiliated Hospital of Guangxi Medical University, 495 Education Road, Yulin, Guangxi 537000, People’s Republic of ChinaTel/Fax +86 0775 268 3223Email yulinlm@yeah.netPurpose: Information regarding the use of aspirin for patients with no known cardiovascular disease remains conflicting. We performed an updated meta-analysis to evaluate the efficacy and safety of aspirin for primary prevention of cardiovascular disease.Patients and methods: PubMed, MEDLINE, and Cochrane library databases were searched for randomized controlled trials comparing aspirin with placebos or no treatment published up until November 1, 2018. The primary efficacy endpoint was all-cause death. The secondary endpoints included cardiovascular death, myocardial infarction, and stroke. The safety endpoints included major bleeding, gastrointestinal bleeding, and hemorrhagic stroke.Results: Fourteen studies were included. Aspirin use was associated with a lower risk of myocardial infarction than placebo use or no treatment (risk ratio [RR], 0.83, 95% confidence interval [CI]: 0.73–0.95, P = 0.005). Additionally, compared with the control groups, aspirin use was not associated with a lower risk of all-cause mortality or cardiovascular mortality. In terms of safety, aspirin use was associated with a higher risk of major bleeding (RR, 1.40, 95% CI: 1.25–1.57, P = 0.000), gastrointestinal bleeding (RR, 1.58, 95% CI: 1.25–1.99, P = 0.000), and hemorrhagic stroke (RR, 1.30, 95% CI: 1.06–1.60, P = 0.011). Furthermore, the treatment effect was not significantly modified by patients’ clinical characteristics. No publication bias was present.Conclusion: Aspirin use reduced the myocardial infarction risk in patients without known cardiovascular disease, but had no effect in terms of reducing the risk of all-cause death, cardiovascular death, and stroke, and increased the risk of major bleeding, gastrointestinal bleeding, and hemorrhagic stroke.Keywords: aspirin, primary prevention, cardiovascular disease, meta-analysis